Control of smooth cordgrass (Spartina alterniflora) seedlings with four herbicides - Knott, Carrie A.; Webster, E. P.; Nabukalu, P. (Journal of Aquatic Plant Management, 2013)
Smooth cordgrass (Spartina alterniflora Loisel.) is a perennial grass native to intertidal saline marshes along the Atlantic and Gulf of Mexico coasts in the United States (Godfrey and Wooten 1979). It has a dense canopy formed by quickly spreading rhizomes. In its native ecosystems, it provides valuable wildlife habitat and is essential to reducing wave energy and accumulating suspended sediments (Redfield 1972, Nepf 1999). Smooth cordgrass has spread worldwide; it was accidentally introduced on the West Coast of the United States in the 1800s (Frenkle and Kunze 1984, Sayce 1988) and has since spread as far north as British Columbia and as far south as California (Frenkle and Kunze 1984). It was also intentionally introduced in China in the 1970s to reclaim coastal areas (Chung 1993, Chung et al. 2004, Zhang et al. 2004). Outside its native ecosystems, smooth cordgrass is an extremely aggressive invader that alters ecosystems so significantly that native biodiversity and habitats can be lost (Callaway and Josselyn 1992, Daehler and Strong 1996, Dumbauld et al. 1997, Chen et al. 2004). Methods to control smooth cordgrass in nonnative areas have included mechanical, biological, and chemical approaches (Norman and Patten 1996, Portnoy 1999, Hedge et al. 2003, Major et al. 2003, Li and Zhang 2008). Success of smooth cordgrass control has varied and appears dependent on environmental conditions and the frequency with which the control measure is implemented. Typically, mechanical methods, which include various combinations of plant removal, mowing, burial, and flooding, have provided acceptable levels of control of smooth cordgrass; however, they are so expensive that widespread implementation is not feasible (Hedge et al. 2003). Biological controls, which have had limited success, include introduction of insects that suppress growth of smooth cordgrass and substitution of smooth cordgrass with native grasses (Grevstad et al. 2003, Li and Zhang 2008). Chemical control, which uses herbicides to eliminate invasive smooth cordgrass, has had greater success in reliably controlling smooth cordgrass plants in natural environments (Kilbride et al. 1995, Patten 2002 Major et al. 2003). To date, 2 herbicides have been registered by the US Environmental Protection Agency (USEPA) for smooth cordgrass control in estuarine environments in the United States: glyphosate and imazapyr. The focus of most control programs is on established smooth cordgrass plant communities. However, seed dispersal is an important mechanism of invasive smooth cordgrass spread (Daehler and Strong 1997, Anttila et al. 1998). Manual removal of smooth cordgrass seedlings has been used as a control option; however, implementation has been prohibited by its labor requirements and cost (Hedge et al. 2003). Because of its success for established plant communities, chemical control of smooth cordgrass seedlings could be an economical and environmentally acceptable option for controlling invasive smooth cordgrass, which will likely require much lower herbicide rates than established smooth cordgrass plants. The objectives of this study were to determine (1) control rates of smooth cordgrass seedlings with 4 herbicides; and (2) injury to established smooth cordgrass plants after the application of 4 herbicides